Mengungkap Hubungan Tersembunyi Antara Harga Kripto dan Saham Pertambangan: Bukti dari ANTM dan TINS - Diky Paramitha; Etik Ipda Riyani; Kan Wen Huey (Efektor, 2025)
The high volatility of the crypto market has raised questions about its potential impact on other financial instruments, including shares of mining sector issuers. This study aims to reveal the relationship between the price of crypto assets, especially Bitcoin, and the stock price movements of two major mining issuers in Indonesia, namely Antam (ANTM) and Tin (TINS). The analysis was carried out with a quantitative approach with a simple linear regression analysis method, to test the influence of the price of bitcoin on each stock. The results of the analysis show the direction of a positive and significant relationship between the price of Bitcoin and ANTM shares with a regression coefficient of 0.008776. This value indicates that any increase in the price of Bitcoin is potentially followed by an increase in the price of ANTM's shares, with a contribution of variation of 45% (R² = 0.45). Meanwhile, the influence on TINS shares was also positive but weaker, with a regression coefficient of 0.004999 and a contribution of variation of 28% (R² = 0.28). These findings indicate that the crypto market could be one of the external factors influencing the dynamics of real sector stocks, especially those related to metal commodities. The conclusion of this study confirms the importance of including crypto variables in the risk analysis and investment strategies of mining sector stocks due to the adoption of blockchain technology that requires such commodities.